Care Nursing In The Family With Environmental Health Issues - Ariyanti, Sri; Kaharuddin, Riski Muhammad Akbar (International Journal of Health Sciences, 2025)
Problem health environment is one of challenge main in nursing community, especially for families living in the neighborhood with sanitation poor, limited clean water, and exposure waste house ladder or industry. The role of nurses community is very important in give care nursing based on family for identify, analyze, and address problem health caused by an unhealthy environment​ healthy. This article aiming for describe care nursing family in handle problem health environment with nursing process approach in a way comprehensive. The results show that intervention directed nursing​ capable increase quality life and behavior life clean and healthy (PHBS) family.